Analisis Pendapatan dan Tingkat Kesejahteraan Petani Kelapa Sawit di Kecamatan Air Hitam Kabupaten Sarolangun - Syabawaihi Syabawaihi; Febrina Nur Annisa; Zaky Maulana; Leo Hartono (BUDGETING : Journal of Business, Management and Accounting, 2023)
The purpose of this study was to describe the cultivation of oil palm independent smallholders of oil palm plantations in the sub-district of Air Hitam Sarolangun and analyze the revenues and profits of farming oil palm independent smallholders in sub-district of Air Hitam Sarolangun. This research was conducted in the sub-district of Air Hitam Sarolangun in May 2023 to Juny 2023. The research results adapted to the existing data and the objectives to be achieved. To achieve the first aims used descriptive method and the second, the data were analyzed with descriptive methods of tabulation.The survey results revealed that the non-farming oil palm farmers spend an average total production amounted to 19.188.393 rupiahs/year, receiving an average of 62.418.953 rupiahs / year, with a total average production of 51.975 kg/ ha / Th , Farm income palm independent smallholders of 43.230.560 rupiahs / year. Analysis of R/C on the cash costs for independent smallholders gardens is 3,41 meaning for every rupiahs cash cost incurred will be obtained receipts of 3,41 rupiah. While the R/C on the total cost for non-farmers' lands is 3,25, which means for every total cost incurred will be obtained receipts of 3,25 rupiahs. Keywords: Farming, Oil palm, Revenue.